Pengaruh Brand Ambassador Terhadap Keputusan Pembelian pada TikTok Shop di Kalangan Mahasiswa Bandung Raya, Indonesia - Safitri, Dwiyanti Budi (International Journal Administration, Business & Organization, 2023)
This research aims to understand and analyze the impact exerted by Brand Ambassadors on purchasing decisions on TikTok Shop among students in the Greater Bandung area, Indonesia. Using primary data collected through the distribution of questionnaires to 110 respondents, employing a quantitative descriptive research method, and analyzing the questionnaire data descriptively, correlatively, hypothesis testing, and normality using IBM SPSS 26 software. The results of this study indicate that brand ambassadors have an influence on purchasing decisions on TikTok Shop, with a total influence of 44.1%, as "quite influential”.